A systematic search and critical review of studies evaluating psychometric properties of patient-reported outcome measures for schizophrenia. (March 2022) - Buck, Benjamin; Gagen, Emily C.; Halverson, Tate F.; Nagendra, Arundati; Ludwig, Kelsey A.; Fortney, John C.
Abstract: Measurement-based care (MBC) involves the regular administration of outcome assessments to track and evaluate treatment progress and requires psychometrically sound instruments. While there are widely used patient-reported outcome measures (PROMs) for several psychiatric disorders and symptom categories (e.g., depression, anxiety), there is less consensus about self-report assessments for measurement-based care of schizophrenia. The present review provides an initial guide to this area by reporting on psychometric studies that introduce or evaluate PROMs designed for the ongoing treatment of schizophrenia. Out of an initial database of 6, 153 articles, and review of 141 full-text articles, an analysis of 21 articles examining 12 measures is presented in this review. Findings suggest robust options exist for clinical and research institutions aiming to assess symptom outcomes in schizophrenia, with most measures showing strengths in internal consistency, test-retest reliability, and a number of measures with evidence of convergent or criterion validity. While there exist heterogeneous options, multiple measures demonstrated promising psychometric strengths. Future work validating consistent psychometric validity could involve measures which could be valuable in context of MBC for schizophrenia.